State-of-the-art: Radiological investigation of pleural disease - Hallifax, R; Talwar, A; Wrightson, J; Edey, A; Gleeson, F (Elsevier, 2017)
Pleural disease is common. Radiological investigation of pleural effusion, thickening, masses, and pneumothorax is key in diagnosing and determining management. Conventional chest radiograph (CXR) remains as the initial investigation of choice for patients with suspected pleural disease. When abnormalities are detected, thoracic ultrasound (US), computed tomography (CT), magnetic resonance imaging (MRI) and positron emission tomography (PET) can each play important roles in further investigation, but appropriate modality selection is critical. US adds significant value in the identification of pleural fluid and pleural nodularity, guiding pleural procedures and, increasingly, as "point of care" assessment for pneumothorax, but is highly operator dependent. CT scan is the modality of choice for further assessment of pleural disease: Characterising pleural thickening, some pleural effusions and demonstration of homogeneity of pleural masses and areas of fatty attenuation or calcification. MRI has specific utility for soft tissue abnormalities and may have a role for younger patients requiring follow-up serial imaging. MRI and PET/CT may provide additional information in malignant pleural disease regarding prognosis and response to therapy. This article summarises existing techniques, highlighting the benefits and applications of these different imaging modalities and provides an up to date review of the evidence.